Aesthetic and Interpretive Approaches in French Music for Saxophone. Robert Planel – Prelude et Saltarella - Constantin, Bogdan; Albu, Doru (Advances in Social Sciences Research Journal, 2024)
Although he knows the saxophone thanks to the leadership of the orchestra, P. Boulez won’t write for sax players because the instrument evokes too much variety and jazz, and at the Conservatory he will not be close to the sax players of the "marginal" class (to use his words) of Professor M. Mule. However, the Paris Conservatoire is an undeniable cradle of composition in terms of works including the saxophone. The number of composers who liked this instrument, students in the classes of Nadia Boulanger, mainly, but also of Olivier Messiaen, Darius Milhaud, Paul Dukas and Andre Jolivet, is impressive, so it is clear how important their influence is and the number of works dedicated to saxophone.